Phytochemical profile and hepatoprotective effects of Crotalaria vialattei against antituberculosis drug-induced liver injury - Zouioueche, Kaouther; Laraba, Meriem; Bensegueni, Afifa; Ramli, Iman; Hammoud, Leila; Erenler, Ramazan; Yıldız, İlyas and Messaoud Nacer, Imene and Berkane, Aya and Bensouici, Chawki and Benayache, Fadila and Benayache, Samir and Zama, Djamila (Archives of Biological Sciences, 2026)
Paper description: Crotalaria vialattei, is an endemic Algerian plant whose phytochemical composition and biological properties remain poorly documented. The n-butanol extract of vialattei was characterized by LC–MS/MS and evaluated for its antioxidant activity and hepatoprotective effects in a rat model of antituberculosis drug-induced hepatotoxicity. The extract exhibited a phenolic-rich profile, measurable antioxidant activity, and significant protective effects against RHZ-induced hepatic alterations. These findings provide new experimental evidence supporting the potential relevance of vialattei as a source of bioactive compounds with hepatoprotective activity. Abstract: Tuberculosis is a global public health concern, and its treatment is frequently associated with hepatotoxic side effects. Phytotherapy represents a promising complementary approach. This study aimed to characterize the phenolic profile of the n-butanol extract of Crotalaria vialattei (BCV), evaluate its antioxidant capacity, and assess its hepatoprotective effects against liver damage induced by a fixed-dose antituberculosis drug combination containing rifampin, isoniazid, and pyrazinamide (RHZ). Phytochemical analysis revealed a phenolic-rich extract, identifying 17 polyphenolic compounds. BCV exhibited measurable antioxidant activity in vitro. In vivo, oral administration of RHZ (rifampin 150 mg/kg, isoniazid 75 mg/kg, and pyrazinamide 400 mg/kg) induced marked alterations in hepatic biochemical markers, lipid profile, oxidative status, and liver histoarchitecture. BCV treatment significantly attenuated these changes by improving liver enzyme activities, restoring oxidative balance, and preserving liver architecture. Overall, the BCV extract demonstrates antioxidant-associated hepatoprotective potential against RHZ-induced liver injury and may represent a promising complementary strategy to reduce antituberculosis drug-related hepatotoxicity.